Residual Stress, Thermomechanics & Infrared Imaging, Hybrid Techniques and Inverse Problems, Volume 9 Proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics - Quinn, Simon; Balandraud, Xavier (Conference Proceedings of the Society for Experimental Mechanics Series,, 2017)
Residual Stress, Thermomechanics & Infrared Imaging, Hybrid Techniques and Inverse Problems, Volume 9 of the Proceedings of the 2016 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the ninth volume of ten from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: Damage Analysis from Thermal Measurements Quantitative Visualization Stress Analysis from Thermal Measurements New Approaches to Residual Stress Measurement Residual Stress & Optical Methods Non-homogeneous Parameters Identification General Inverse Methods Residual Stress Measurement by X-Ray Diffraction.